The landscape genetics of syntopic topminnows (Fundulus notatus and F. olivaceus) in a riverine contact zone. Issue 4 (10th November 2013) - Earnest, Kate; Scott, Jason; Schaefer, Jake; Duvernell, David
Abstract The metapopulation dynamics of a species are influenced by the spatial arrangement of preferred habitats across a landscape. Increasing habitat patchiness can result in greater population subdivision, leading to more pronounced population genetic structure. Therefore, even subtle differences in habitat preferences among species could lead to substantial differences in genetic structure. Members of the Fundulus notatus species complex of topminnows include a headwater specialist and a large river specialist with broadly overlapping geographical distributions. Both species are often found in the same drainage systems, but partially isolated by divergent habitat preferences. The purpose of this research was to determine whether distribution along a stream continuum in a contact zone influences population genetic patterns in two species of topminnow (Fundulus olivaceus and Fundulus notatus). Fish were collected in the summers of 2010–2012, and habitat data were collected in summer 2012, within all major tributaries of the Saline River in southern Illinois. In total, 523 fish were genotyped using seven microsatellite loci to assess genetic variation. Species distributions in F. notatus and F. olivaceus were associated with habitat factors that covaried with cumulative drainage area. Populations of F. olivaceus showed a greater level of genetic structure reflected in a significant pattern of isolation by distance, while populations of F. notatus showed no such pattern. Spatial autocorrelation analysis revealed that at an individual level, both species became increasingly divergent with waterway distance. Overall, clear interspecific differences in habitat preferences were translated into measurable but relatively subtle differences in population genetic structure.